ESIMPLER: A Dynamic, Electronic Health Record–Integrated Checklist for Clinical Decision Support During PICU Daily Rounds. Issue 10 (3rd May 2021) - Geva, Alon; Albert, Ben D.; Hamilton, Susan; Manning, Mary-Jeanne; Barrett, Megan K.; Mirchandani, Dimple; Harty, Matthew; Morgan, Erin C.; Kleinman, Monica E.; Mehta, Nilesh M.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Design, implement, and evaluate a rounding checklist with deeply embedded, dynamic electronic health record integration. DESIGN: Before-after quality-improvement study. SETTING: Quaternary PICU in an academic, free-standing children's hospital. PATIENTS: All patients in the PICU during daily morning rounds. INTERVENTIONS: Implementation of an updated dynamic checklist (eSIMPLER) providing clinical decision support prompts with display of relevant data automatically pulled from the electronic health record. MEASUREMENTS AND MAIN RESULTS: The prior daily rounding checklist, eSIMPLE, was implemented for 49, 709 patient-days (7, 779 patients) between October 30, 2011, and October 7, 2018. eSIMPLER was implemented for 5, 306 patient-days (971 patients) over 6 months. Checklist completion rates were similar (eSIMPLE: 95% [95% CI, 88–98%] vs eSIMPLER: 98% [95% CI, 92–100%] of patient-days; p = 0.40). eSIMPLER required less time per patient (28 ± 1 vs 47 ± 24 s; p < 0.001). Users reported improved satisfaction with eSIMPLER ( p = 0.009). Several checklist-driven process measures—discordance between electronic health record orders for stress ulcer prophylaxis and user-recorded indication for stress ulcer prophylaxis, rate of venous thromboembolism prophylaxis prescribing, and recognition of reduced renal function—improved during the eSIMPLER phase. CONCLUSIONS: eSIMPLER, a dynamic, electronic health record–informed checklist, required less time to complete and improved certain care processes compared with a prior, static checklist with limited electronic health record data. By focusing on the "Five Rights" of clinical decision support, we created a well-accepted clinical decision support tool that was integrated efficiently into daily rounds. Generalizability of eSIMPLER's effectiveness and its impact on patient outcomes need to be examined.